2017
DOI: 10.1002/ptr.6004
|View full text |Cite
|
Sign up to set email alerts
|

Alantolactone, a sesquiterpene lactone, inhibits breast cancer growth by antiangiogenic activity via blocking VEGFR2 signaling

Abstract: Alantolactone (ALA), a sesquiterpene lactone isolated from several medicinal plants such as Inula helenium, has been identified to have attractive anticancer activity. However, its role in the inhibition of angiogenesis during tumor development remains unclear. In this study, we found ALA can inhibit the proliferation, motility, migration, and tube formation of human umbilical vein endothelial cells. ALA also restrained angiogenesis in chick embryo chorioallantoic membrane and delayed the growth of human MDA-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 26 publications
3
11
0
Order By: Relevance
“…It was found that santonin exerts significant anticancer effects on the SK-BR-3 ovarian cancer cells by inhibiting the proliferation of the SK-BR-3 cancer cells concentration dependently. These observations confirmed previous investigations wherein sesquiterpene lactone was shown to halt the growth of the cancer cells; for example, alantolactone which is a plant derived sesquiterpene has been reported to suppress the growth of the breast cancer cells [16]. Similarly, calein C, which is another sesquiterpene lactone has been reported to suppress the growth of cancer cells [17].…”
Section: Discussionsupporting
confidence: 89%
“…It was found that santonin exerts significant anticancer effects on the SK-BR-3 ovarian cancer cells by inhibiting the proliferation of the SK-BR-3 cancer cells concentration dependently. These observations confirmed previous investigations wherein sesquiterpene lactone was shown to halt the growth of the cancer cells; for example, alantolactone which is a plant derived sesquiterpene has been reported to suppress the growth of the breast cancer cells [16]. Similarly, calein C, which is another sesquiterpene lactone has been reported to suppress the growth of cancer cells [17].…”
Section: Discussionsupporting
confidence: 89%
“…As a critical component of tumor angiogenesis, glycoprotein vascular endothelial growth factor (VEGF) is widely expressed in many cancers [100,101], while the vascular endothelial growth factors receptor-2 (VEGFR2) increased signaling is also characteristic of angiogenesis in tumors [102,103,104]. Alantolactone ( 11 ) (Figure 2) exhibits anti-angiogenesis property, since it shows anti-proliferative activity against human umbilical vascular endothelial cells (HUVEC) (IC 50 = 14.2 μM), a model cell line used to study angiogenesis processes [105]. The alantolactone ( 11 ) anti-angiogenesis property could be related with its capacity to decrease capillary formation, by suppressing VEGFR2 signaling and decreasing the expression of its multiple downstream protein kinases, e.g., focal adhesion kinase (FAK) [105].…”
Section: Secondary Metabolites From Inula Species Against Oxidativmentioning
confidence: 99%
“…Notably, ALT was suggested to exhibit potential anti-cancer activity against various types of cancer, including human colorectal cancer (10), liver cancer (11,12), leukemia (13), breast cancer (14), lung cancer (15,16) and cervical cancer (17,18). ALT may inhibit breast cancer growth via anti-angiogenic activity by inhibiting vascular endothelial growth factor receptor 2 and RAC-alpha serine/threonine-protein kinase B (AKT) signaling (19). In human cervical cancer cells, ALT induces apoptosis via generation of reactive oxygen species (ROS) and inhibition of the B-cell lymphoma 2 (Bcl-2)/Bcl-2 associated X apoptosis regulator (Bax) signaling pathway (17).…”
Section: Introductionmentioning
confidence: 99%